Plastic marine debris study based on Indonesian plastic national balance (IPNB) and seashore approach. Issue 1 (April 2021) - Abidin, A Z; Steven, S
Abstract: A clear and accurate plastic marine debris amount to clarify Indonesian marine debris issues still does not exist. Only Jambeck's study estimated that millions of tonnes of plastic enter the Indonesian ocean every year, but the result is often disputed. This study, hence, was conducted to calculate the Indonesian plastic marine debris amount using Indonesian plastic national balance (IPNB) and seashore approach. The study was based on Indonesia's 2019 data of plastic production, plastic raw material and finished-product balance, plastic recycling industry, plastic consumption, and plastic distribution. Indonesian plastic industries have a total capacity of 2.66 MT/y, production of 2.31 MT/y, import of 1.67 MT/y, and recycle of 1.655 MT/y. The results from Indonesian plastic national balance (IPNB) imply that after-used plastic of 5.755 MT/y is categorized into material still-consumed, material recycled, and plastic waste. About 90% of the plastic waste is managed which further recycled (0.654 MT/y) and ended up in the landfill (0.868 MT/y), while the rest (about 10%) is mismanaged and become marine debris (0.17 MT/y). For the results from the seashore approach, after-used plastic is burned and buried (3.228 MT/y), recycled (1.655 MT/y), ended up in the landfill (0.868 MT/y), flowed to the river (0.009 MT/y), picked up in the river (0.005 MT/y), and the rest become marine debris (0.004 MT/y). Both results differ from Jambeck's calculation (0.48-1.29 MT/y) and therefore, clarify that Indonesia is not the second-largest contributor country for plastic marine debris.